Estetika Ragam Tengkuluk Pakaian Tradisional Masyarakat Melayu Jambi - Hartati M; Fatonah Fatonah; Selfi Mahat Putri (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
This study aims to determine the history and aesthetic values of tengkuluk as the traditional costumes of Malay women in Jambi. The benefits of this research are expected to be one of the inventory cultural of Malay culture in Jambi, in the scope scientific science. The method in this study was qualitative method with a symbolic interaction approach. With the background of the diversity of natural and cultural wealth possessed by the Jambi province, there covers some values of beauty, philosophy and cultural aesthetic values. One of the aesthetics of the tekuluk / tengkuluk is as headgear that has an important part in the traditional costumes of Malay women in Jambi. The use of tengkuluk as a symbol of the head covering has a philosophical meaning that was closely related to traditional customs and Islamic. The entry of Islamic in the Malay land affected the concept of custom in using of female Malay headgear in Jambi. It can be concluded that tengkuluk was not only as a headgear but also as a cover for part of the body which is forbidden to see, which were inventoried in the Jambi traditional seloko which is  "Adat Bersendi Syara’, Syara’ Bersendi Kitabullah. Syara’ Mengato, Adat Memakai.” That rhymes became a philosophical value in the art of aesthetic tying for Malay women in Jambi which had a uniqueness of aesthetic and artistic values without using the help of a safety pin. In addition, when Islam had developed in Malay landl, the clothes of the brackets and tengkuluk became one cohesion that functioned not only as a head covering or body wrap, but it was a necessity as the identity of Malay Muslim identity, the tengkuluk became a part of the female genitalia in accordance with Islamic law thriving in Malay land.